Pengaruh Konsumsi Kacang Hijau Terhadap Ibu Hamil Guna Pemenuhan Hemoglobin Di Kecamatan Masama - Maghfira Idrus Fira; Nurmasyitah Mambuhu (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Anemia is one of the common blood disorders that occurs when the levels of red blood cells (erythrocytes) in the body become too low. This can cause health problems because red blood cells contain hemoglobin, which carries oxygen to body tissues. The purpose of this study was to determine the effect of giving green beans on hemoglobin levels in pregnant women in the working area of the Tangeban Health Center. The research design used was pre-experimental research with One Group Pre Test Post Test Design approach. This research was carried out by giving a pre-test before treatment, after treatment was given a post test. In this study, the samples taken were some pregnant women with low hemoglobin levels in the working area of the Tangeban Health Center, Banggai Regency. Based on the results of statistical tests using statistical paired t-tests, it is known that the magnitude of the significant value is 0.000 with α = 0.05. Because of the significant value of < α, H0 is rejected and H1 is accepted, which means that there is an effect of increasing hemoglobin levels before and after giving green beans to pregnant women at the Tangeban Health Center, Masama District, Banggai Regency. The conclusion is that giving green beans to pregnant women provides an increase in hemoglobin levels.